2015
DOI: 10.1007/s13577-015-0116-4
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced viability and neural differential potential in poor post-thaw hADSCs by agarose multi-well dishes and spheroid culture

Abstract: Human adipose-derived stem cells (hADSCs) are potential adult stem cells source for cell therapy. But hADSCs with multi-passage or cryopreservation often revealed poor growth performance. The aim of our work was to improve the activity of poor post-thaw hADSCs by simple and effective means. We describe here a simple method based on commercially available silicone micro-wells for creating hADSCs spheroids to improve viability and neural differentiation potential on poor post-thaw hADSCs. The isolated hADSCs pos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
19
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(19 citation statements)
references
References 73 publications
0
19
0
Order By: Relevance
“…Currently, various spheroid culture methods have emerged to form cell aggregates and study their effect on MSCs, including the use of non-adherent plates or microfabrication-based non-adhesive surfaces, the hanging-drop method, spinner or rotary dynamic culture systems, or the use of agarose multi-well dishes from rubber micro-molds (Song et al, 2004; Nyberg et al, 2005; Bogdanova-Jatniece et al, 2014; Rettinger et al, 2014; Guo et al, 2015; Nakagawa et al, 2016). Compared to other methods, the hanging-drop method is relatively economical and convenient.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Currently, various spheroid culture methods have emerged to form cell aggregates and study their effect on MSCs, including the use of non-adherent plates or microfabrication-based non-adhesive surfaces, the hanging-drop method, spinner or rotary dynamic culture systems, or the use of agarose multi-well dishes from rubber micro-molds (Song et al, 2004; Nyberg et al, 2005; Bogdanova-Jatniece et al, 2014; Rettinger et al, 2014; Guo et al, 2015; Nakagawa et al, 2016). Compared to other methods, the hanging-drop method is relatively economical and convenient.…”
Section: Discussionmentioning
confidence: 99%
“…Calabrese et al fabricated a new Collagen I-based 3D scaffold and assessed its chondrogenic potential in vitro , which promoted the early chondrogenic differentiation of hADSCs (Calabrese et al, 2017). Guo et al reported that spheroid formations may enhance the neural differentiation potential of post-thaw hADSCs (Guo et al, 2015). Other research has shown that hypoxia reinforces proliferation and VEGF expression of hADSCs (Lee et al, 2009) suggesting that the stemness of hADSCs might be intensified via a hypoxic environment in the inner parts of MTs.…”
Section: Discussionmentioning
confidence: 99%
“…ADSCs were conducted the adipogenic induction at passage 2 (P2) as the reported protocols . ADSCs (1 × 10 6 cells/well) were seeded into six‐well cell culture dishes.…”
Section: Methodsmentioning
confidence: 99%
“…Flow cytometry was conducted as the reported method . Briefly, cell samples were fixed using 4% paraformaldehyde in PBS, and permeabilized using 0.1% TritonX‐100 (Sigma).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation